The mediating role of positive body image between friendship qualities, well-being strategies and identity development among adolescents - Eryılmaz, Ali; Kara, Ahmet; Uzun, Abdullah Ensar (Springer Science and Business Media LLC, 2024)
AbstractThis study aimed to explore the mediating role of body image in the association between The utilization of strategies aimed at enhancing subjective well-being, friendship qualities, and identity development. The participants consisted of 270 early adolescents, comprising 157 girls (58.15%) and 113 boys (41.85%). Data were collected using several scales, including the “Body Appreciation Scale,” “Subjective Well-Being Increasing Strategies Scale for Adolescents,” “Friendship Qualities Scale,” and “The Dimensions of Identity Development Scale.” Two-stage structural equation modeling was employed to analyze the gathered data. The findings indicated a positive model of identity development in adolescents, highlighting that subjective well-being increasing strategies contribute positively to identity development, and this relationship is mediated by positive body image. Furthermore, the study found that positive body image also mediates the association between adolescents’ identity development and the establishment of quality friendships.
Keywords: 4. Education; 3. Good health